2009
DOI: 10.1103/physrevlett.103.073001
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Sublevels of an Ortho-Hydrogen Molecule Encapsulated in an IsotropicC60Cage

Abstract: From specific heat measurements in high quality H2@C60 samples performed over a broad temperature range, we obtain the smallest yet observed splitting of rotational energy sublevels of encapsulated single H2 molecules, 0.1-0.2 meV, in the nearly spherical potential well provided by highly isotropic C60 cages. Additionally, we find evidence of the quantized oscillation state of isolated H2 in the C60 cage. The minuscule splitting indicates that H2@C60 provides unprecedented opportunities to study free-molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 16 publications
5
29
0
Order By: Relevance
“…If these effects are important their contribution to the IR spectra is of the order of one wavenumber splitting of a few absorption lines. Such small splitting is consistent with the NMR [28,29] and heat capacity [30] results. C 70 has an ellipsoidal shape and this splits the translation-rotation states of H 2 .…”
Section: Discussionsupporting
confidence: 90%
“…If these effects are important their contribution to the IR spectra is of the order of one wavenumber splitting of a few absorption lines. Such small splitting is consistent with the NMR [28,29] and heat capacity [30] results. C 70 has an ellipsoidal shape and this splits the translation-rotation states of H 2 .…”
Section: Discussionsupporting
confidence: 90%
“…(d) Rotational fine structure: the rotational peak studied at low temperature Using heat capacity measurements at low temperature, Kohama et al [29] have suggested there is evidence for a splitting of the order of 0.1-0.2 meV of the principal rotational peak centred on | E 0−1 | = 14.7 meV. The C 60 cage is icosahedral so the potential energy surface has too high a symmetry to be responsible for such a splitting.…”
Section: Results and Discussion (A) The Low Temperature Inelastic Neumentioning
confidence: 99%
“…Such small splitting is consistent with the results of heat capacity measurements. 43 We do not explain how the determined parameters are linked to the molecular structure of the H 2 @C 60 complex. In principle it should be possible to describe, within a single quantum chemical model of H 2 @C 60 , the potential parameters, induced dipole parameters, the dependence of both on the vibrational state, and the changes of rotational and vibrational constants compared to free H 2 values.…”
Section: Discussionmentioning
confidence: 99%